Simple reconstruction of the skin and soft-tissue defect following Fournier’s gangrene - Sundar, Geeta; Rao, Harish K (Indian Journal of Case Reports, 2024)
Fournier’s gangrene (FG) is a form of severe necrotizing fasciitis over the external genitalia, perineal, and perianal region with vessel thrombosis, sepsis, and multiorgan failure. Mortality and morbidity are high, treatment includes intensive resuscitation, emergency debridement, and parenteral antibiotics. The defects are closed later using negative pressure, skin grafting, muscle flaps, primary closure, thigh pockets, or a combination. The below case series included four patients who presented with FG involving the perineum and external genitalia, underwent serial debridement of the necrotic scrotal tissue exposing the testes, and once the wound was clean, a local cover for the testes either primary closure by mobilization of healthy skin around the scrotum, or by medial thigh pockets was done. The advantages of utilizing the local skin are reduced friction, good cosmesis, decreased infection, ensured functionality, easier to perform surgically, have reduced hospital stay; as compared to grafting, which leads to contractures with healing, decreased lubrication, and higher patient dissatisfaction. Utilizing the local skin around the scrotum and perineum can act as an efficient means of satisfactory restorative cosmesis and function in FG.